Incidental Discovery of Hepatocellular Carcinoma on 18F-PSMA PET CT Performed for Prostate Cancer Reassessment - Lauren Hekman; Eva Napierkowski; Natalie C. Hartman; Jeffrey L. Ellis; Robert H. Wagner; Davide Bova; Maria M. Picken; Robert C. Flanigan (Case Reports in Surgery)
Prostate-specific membrane antigen positron emission tomography (PSMA PET) has been approved by the Food and Drug Administration (FDA) to identify prostate cancer in the setting of biochemical recurrence but can also identify other malignancies. 18F-PSMA PET has not been studied as a potential tool for hepatocellular carcinoma (HCC). We describe the case of a 76-year-old male with a rising prostate-specific antigen (PSA) after definitive prostate cancer treatment and no prior liver pathology who was incidentally found to have HCC on 18F-PSMA PET.